2017
DOI: 10.21873/cgp.20030
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Evaluation of Epidermal Growth Factor Receptor (EGFR) Genotype and Phenotype Parameters in Triple-negative Breast Cancers

Abstract: Abstract. Background: Epidermal growth factor receptor (EGFR) aberrations have been implicated in the pathogenesis

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 87 publications
0
29
0
Order By: Relevance
“…Our study is the first to report that TNBCs have a much higher risk of secondary lung cancers. Epidermal growth factor receptor (EGFR) expression is reported in greater than 50% of TNBCs and correlates negatively with survival in these patients ( 15 17 ). Overexpression of EGFR in lung adenocarcinomas and TNBCs may provide one clue for common etiologic pathways ( 18 , 19 ).…”
Section: Discussionmentioning
confidence: 99%
“…Our study is the first to report that TNBCs have a much higher risk of secondary lung cancers. Epidermal growth factor receptor (EGFR) expression is reported in greater than 50% of TNBCs and correlates negatively with survival in these patients ( 15 17 ). Overexpression of EGFR in lung adenocarcinomas and TNBCs may provide one clue for common etiologic pathways ( 18 , 19 ).…”
Section: Discussionmentioning
confidence: 99%
“…Molecular testing was performed in laboratories internationally certified for EGFR mutation testing; 70% of the tumors were analyzed in the AUTH Department of Pathology or Hellenic Foundation for Cancer Research/Hellenic Cooperative Oncology Group Laboratory of Molecular Oncology, and 30% were analyzed in private laboratories, as previously described. 13 Details are provided in the Data Supplement.…”
Section: Methodsmentioning
confidence: 99%
“…9 Two separate studies revealed EGFR activation in 2 GRCC cases, with one of the cases harboring a unique EGFR mutation and gene amplification. 17,18 Our study, based on NGS analysis of 5 GRCC cases, revealed no EGFR genomic alterations in this cancer. 9 ERBB3 (HER3) and ERBB4 (HER4) mutations were not detected in GRCC either.…”
Section: Her Receptors Family In Grccmentioning
confidence: 66%
“…Two studies revealed a low proliferation rate of GRCC, 17,19 whereas the study of Toikkanen and Joensuu 6 indicated a nondiploid nature of GRCC with a high S-phase fraction. Another study carried out by Kim et al 18 Similar to other breast cancer subtypes and cancer in general, the TP53 gene appears to be involved in a subset of GRCCs.…”
Section: Molecular Genetic Characteristics Of Grccmentioning
confidence: 99%